2020
DOI: 10.1016/s0140-6736(20)30922-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and COVID-19: an urgent public health research priority

Abstract: Ethnicity is a complex entity composed of genetic make-up, social constructs, cultural identity, and behavioural patterns. 2 Ethnic classification systems have limitations but have been used to explore genetic and other population differences. Individuals from different ethnic backgrounds vary in behaviours, comorbidities, immune profiles, and risk of infection, as exemplified by the increased morbidity and mortality in black and minority ethnic (BME) communities in previous pandemics. 3 As COVID-19 spreads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
422
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(449 citation statements)
references
References 4 publications
17
422
2
8
Order By: Relevance
“…A greater susceptibility to severe disease and mortality in non-White ethnic groups has been recorded in both the US 8,9,24 and the UK. 3,5,7 We observed over two-fold increased risk of severe covid-19 in Indian/Pakistani/Bangladeshi ethnic groups and over three-fold increased risk in Black ethnic groups. Further analyses stratifying Blacks into African and Caribbean subgroups yielded similar effects for both groups (OR 2.95 and 3.38 respectively, both P<0.001).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A greater susceptibility to severe disease and mortality in non-White ethnic groups has been recorded in both the US 8,9,24 and the UK. 3,5,7 We observed over two-fold increased risk of severe covid-19 in Indian/Pakistani/Bangladeshi ethnic groups and over three-fold increased risk in Black ethnic groups. Further analyses stratifying Blacks into African and Caribbean subgroups yielded similar effects for both groups (OR 2.95 and 3.38 respectively, both P<0.001).…”
Section: Discussionmentioning
confidence: 71%
“…1 Examination of the characteristics of people hospitalised with covid- 19 and their outcomes has given some insight into the epidemiology of the disease. [2][3][4] Reports have suggested that ethnicity 3,[5][6][7][8][9] and residential deprivation 10 are associated with death from covid-19, prompting a rapid review to be led by Public Health England. 11 There is also interest in whether use of antihypertensive medications that affect the renin-angiotensin system can increase the risk of severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, ethnicity appeared to have specific association with COVID-19 positive status that appeared independent from the often-quoted confounders of cardiovascular and metabolic morbidity that are known to be higher in prevalence in BME cohorts 15 . Having accounted for cardiometabolic morbidity, the possible explanations for this association remain numerous 16 , gravitating around both genetic and social factors: behavioural, cultural, and socioeconomic differences, including health-seeking behaviour and intergenerational cohabitation are all likely to play a role in the strong disparity observed in our study, providing key targets for both further research and public health policy.…”
Section: Comparison With Existing Literaturementioning
confidence: 91%
“…1 Non-steroidal anti-inflammatory drugs included aspirin, ibuprofen, diclofenac, naproxen, indomethacin, celecoxib, and meloxicam. 2 Angiotensin converting enzyme inhibitors included captopril, enalapril, lisinopril, fosinopril, ramipril, and quinapril. 3 Angiotensin II receptor blockers included losartan, candesartan, eprosartan, irbesartan, olmesartan, telmisartan, and valsartan.…”
Section: Copyright/license For Publicationmentioning
confidence: 99%
“…Baseline Characteristics of UK Biobank Participants Body-mass index is the weight in kilograms divided by the square of the height in meters 1. Chronic obstructive pulmonary disease was defined as a diagnosis of emphysema and/or bronchitis 2. Ischemic heart disease was categorized as history of myocardial infarction or angina.…”
mentioning
confidence: 99%